Microstructure and mechanical properties of refractory HfMo0.5NbTiV0.5Six high-entropy composites - Liu, Yuan; Zhang, Yan; Zhang, Heng; Wang, Naijuan; Chen, Xiang; Zhang, Huawei; Li, Yanxiang (Journal of alloys and compounds, 2017)
HfMo0.5NbTiV0.5Six (x = 0, 0.3, 0.5, 0.7) high-entropy alloys are synthesized by induction levitation melting with the aim of achieving a balanced combination of excellent strength at elevated temperature and reasonable ductility at room temperature (RT). The microstructure, phase evolution and compression mechanical properties of the alloys from 20 °C to 1200 °C are reported in this paper. It is found that the HfMo0.5NbTiV0.5 matrix forms a simple disordered body-centered cubic (BCC) phase. After adding the Si element, multi-component silicide (Hf, Nb, Ti)5Si3 is generated inside the alloys and exhibits a transition from hypoeutectic structure to eutectic structure and then to hypereutectic structure as the Si content increases. The addition of Si significantly improves the hardness and strength but reduces the ductility. At room temperature, The HfMo0.5NbTiV0.5 and HfMo0.5NbTiV0·5Si0.7 alloys show yield strengths of 1260 MPa and 2134 MPa, respectively, and the compressive mechanism transitions from ductile deformation to brittle fracture from x = 0 to x = 0.7. Strain softening and silicide segmentation are found to be typical during compression deformation of these alloys at elevated temperatures. In these conditions, the alloys survive at least 35% of engineering compression strain without fracture. During deformation at 1200 °C, the yield strengths of HfMo0.5NbTiV0.5 and HfMo0.5NbTiV0·5Si0.7 alloys are 60 MPa and 235 MPa, respectively. The attractive strength of the Si-containing alloys at elevated temperatures is strongly dependent on the strengthening effect caused by the silicides. •Refractory HfMo0.5NbTiV0.5Six high-entropy composites are prepared successfully.•Multi-component silicide (Hf, Nb, Ti)5Si3 is generated with adding Si.•The addition of Si reduces the density and improves the hardness and strength.•Silicides play a significant role on strength increment.•The composite structure is beneficial to the comprehensive properties.